Socialization of Processing Used Cooking Oil into Aromatherapy Candles: An Effort to Reduce Waste in Betungan Village, RW. 07, RT. 61 - Anita, Yuti; Rabiah, Nuria Zaidatur; Putri, Wulandari Indah Andi; Elsafa, Vineza; Revanda, Sinti; Herlin, Herlin; Wahyudi, Yusuf; Nur’aini, Hesti (Universitas Dehasen Bengkulu, 2025)
The “Socialization of Used Cooking Oil Processing into Aromatherapy Candles” activity by KKN-T students of Dehasen University Bengkulu was held at RT. 61, RW 07, Betungan Village, Bengkulu City, Bengkulu Province on Monday, June 30, 2025. This socialization activity aims to reduce environmental pollution and prevent diseases caused by repeated use of used cooking oil. This activity was carried out with a direct practice method with residents of RT. 61, starting with the preparation of materials, making aromatherapy candles and opening a question and answer session for participants. After conducting this socialization, it is hoped that used cooking oil waste can reduce household waste and environmental pollution around residents.